Analysis of the allocation and execution of the public budget of the Environment and Sustainable Development Sector, in the period 2018-2020. (2021)
This document contains an analysis of the allocation and execution of the public budget of the Environment and Sustainable Development Sector in the period 2018-2020. It will analyze the allocation of budgets and how they are being executed in the sector. In the first instance, a description of the Colombian budget regulations was made in order to be able to include these elements in the analysis of the appropriations and executions carried out. Secondly, a description of the structure of the environment and sustainable development sector was made. Finally, it was possible to establish its participation with respect to the general budget of the nation and to discriminate the investment and operation items in order to arrive at the execution percentages by entity. With this information it became evident that the structure and coordination of the sector is deficient, the times for the elaboration, approval and execution of the budget are not in accordance with the dynamics of the entities and the allocation of the budget of the environmental sector is really scarce with respect to the responsibility they have with society and the world.